Effects of Monetary Policy Shocks on Domestic and Foreign Banks Lending in Tanzania - Zawadi, Ally (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
This study investigated the effect of monetary policy shocks on bank loans extended by domestic and foreign banks in Tanzania over the period from 2006 to 2020. It adopted the impulse response functions and the variance decomposition analysis to study the responses of these types of lending to monetary policy shocks. The studyfound out that foreign banks do not react negatively to a monetary policy shock, supporting the view that foreign banks in Tanzania did not abandon the domestic market in times of economic distress. The policy implication was that the foreign banks in Tanzania had been supportive of the domestic economy even in times of economic distress. Empirical evidence provided by this study supported the positive role played by the foreign banks in contributing to the financial and economic stability of the Tanzanian economy. The theoretical contribution of the study is that despite a tight monetary condition, the foreign banks continued to resume lending, implying that the “capital flight” argument did not apply to the foreign banks’ operations in Tanzania.